1999
DOI: 10.1038/19789
|View full text |Cite
|
Sign up to set email alerts
|

Composite co-activator ARC mediates chromatin-directed transcriptional activation

Abstract: Gene activation in eukaryotes is regulated by complex mechanisms in which the recruitment and assembly of the transcriptional machinery is directed by gene- and cell-type-specific DNA-binding proteins. When DNA is packaged into chromatin, the regulation of gene activation requires new classes of chromatin-targeting activity. In humans, a multisubunit cofactor functions in a chromatin-selective manner to potentiate synergistic gene activation by the transcriptional activators SREBP-1a and Sp1. Here we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
123
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(130 citation statements)
references
References 24 publications
7
123
0
Order By: Relevance
“…Unlike Mediator, however, TREF does not stimulate GAL4-VP16-dependent transcription in vitro. Together with its cooperativity with Mediator in stimulating transcription from the c-fos promoter and its differing chromatographic behavior from Mediator (30,43), TREF appears to be a novel activity distinct from the well characterized Mediator. Indeed, several steps of chromatography revealed that TREF is separated into three distinct components, one of which, TREF␣, turned out to be hnRNP R. As it is, TREF␣ is also distinct from the reported coactivators for SRF or CREB, including CoS (coactivator for SRF-activated transcription) (44), MRTFs (myocardin-related transcription factors) (45,46), CBP (CREB binding protein)/p300 (47), and TORC (transducer of regulated CREB) (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Mediator, however, TREF does not stimulate GAL4-VP16-dependent transcription in vitro. Together with its cooperativity with Mediator in stimulating transcription from the c-fos promoter and its differing chromatographic behavior from Mediator (30,43), TREF appears to be a novel activity distinct from the well characterized Mediator. Indeed, several steps of chromatography revealed that TREF is separated into three distinct components, one of which, TREF␣, turned out to be hnRNP R. As it is, TREF␣ is also distinct from the reported coactivators for SRF or CREB, including CoS (coactivator for SRF-activated transcription) (44), MRTFs (myocardin-related transcription factors) (45,46), CBP (CREB binding protein)/p300 (47), and TORC (transducer of regulated CREB) (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…The VP16 TAD targets basal Pol II transcription factors, including TFIIA, TFIIB, TFIID, the TFIIH subunit Tfb1/p62 (yeast/human) and the Mediator co-activator [18][19][20][21][22][23] . The VP16 TAD binds the Mediator subunit Med25 (also called Arc92) [24][25][26][27] , which is specific to higher eukaryotes. Med25 consists of two domains, the activator interaction domain (ACID) 24 that binds the VP16 TAD, and a 'von Willebrand factor type A' domain that anchors Med25 to Mediator 24 .…”
mentioning
confidence: 99%
“…SRCs and cointegrators such as p300/CBP and p300/CBP-associated factor (PCAF), which enhance transcriptional activation of NRs, also exhibit histone acetyltransferase activity, which may also contribute to interactions of NRs with their cognate response elements and the basal transcriptional machinery (38 -41). In addition, members of a complex group of related proteins that include vitamin D receptor-interacting proteins (DRIP), cofactors required for Sp1 (CRSP), activated recruited cofactors, and thyroid hormone-associated proteins (TRAP) also coactivate ER and other NRs (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). In contrast, these proteins do not exhibit histone acetyltransferase activity, and a recent study using a chromatin immunoprecipitation assay showed that both SRC-3 and DRIP205 are recruited to the estrogen-responsive region of the cathepsin D gene promoter after treatment of MCF-7 cells with 17␤-estradiol (E2) (53).…”
mentioning
confidence: 99%